I'm trying to prove that the 2nd order polynomial kernel, $K(x_i, x_j) = (x_i^Tx_j + 1)^2$ is a valid kernel which satisfies the following conditions:

  1. K is symmetric, that is, $K(x_i, x_j) = K(x_j, x_i)$.
  2. K is positive semi-definite, that is, $\forall v \space\space v^TKv \geq 0.$

We can actually prove that second-order polynomial kernel function is a valid kernel by deriving the corresponding transformation function $\phi(x) = [1, \sqrt{2}x_1, ..., \sqrt{2}x_d, x_1x_1, x_1x_2, ..., x_1x_d, x_2x_1, ...x_dx_d]^T$ where $d$ is the number of features (dimensionality). But I do want to prove that two conditions listed above holds for the given kernel function.

My attempts:

  1. Symmetry is rather straightforward: $$(x_i^Tx_j + 1)^2 = x_i^Tx_jx_i^Tx_j + 2x_i^Tx_j + 1 = A \in \mathbb{R}$$ $$(x_j^Tx_i + 1)^2 = x_j^Tx_ix_j^Tx_i + 2x_j^Tx_i + 1 = B \in \mathbb{R}$$ It can be observed that $A^T = B$, and since they are scalars, $A = A^T = B \implies A = B$.

  2. For the second condition, my attempt is as follows:

$$v^TK = [\sum_{i=1}^{n}(x_i^Tx_1 + 1)^2 v_i \space\space ... \space\space \sum_{i=1}^{n}(x_i^Tx_n + 1)^2 v_i] \\ v^TKv = \sum_{j=1}^{n}\left(\sum_{i=1}^{n}(x_i^Tx_j + 1)^2 v_i\right) v_j$$$$ v^TKv = \sum_{j=1}^{n}\sum_{i=1}^{n}(x_i^Tx_j + 1)^2 v_i v_j$$ Now I proceed with expanding the term $(x_i^Tx_j + 1)^2$: $$v^TKv = \sum_{j=1}^{n}\sum_{i=1}^{n}(x_i^Tx_jx_i^Tx_j + 2x_i^Tx_j + 1) v_i v_j $$$$ = \sum_{j=1}^{n}\sum_{i=1}^{n}x_i^Tx_jx_i^Tx_jv_i v_j + 2x_i^Tx_jv_i v_j + v_i v_j$$ After this point, I don't know how to proceed. I feel like I have to use double sum property: $$\sum_{i=1}^{n}\sum_{j=1}^{n}a_ib_j = \sum_{i=1}^{n}a_i \cdot \sum_{i=1}^{n}b_i$$

But I can eliminate only the term with $v_iv_j$. $$v^TKv = (\sum_{j=1}^{n}v_i\sum_{i=1}^{n}v_i) + 2(\sum_{i=1}^{n}\sum_{j=1}x_i^Tx_jv_iv_j) + \sum_{i=1}^{n}\sum_{j=1}^{n}x_i^Tx_jx_i^Tx_jv_i v_j$$

$$ =(\sum_{i=1}^{n}v_i)^2 +2(\sum_{i=1}^{n}\sum_{j=1}x_i^Tx_jv_iv_j) + \sum_{i=1}^{n}\sum_{j=1}^{n}x_i^Tx_jx_i^Tx_jv_i v_j$$ First term is greater than or equal to zero, therefore it can be cancelled out. But, for the rest, I cannot come up with any simplification. I have two questions:

  1. How should I proceed further at this point?
  2. How can one prove that any polynomial kernel with degree $p$ is PSD using this approach?

Thank you for your time.

  • $\begingroup$ Hi. Welcome to CV. Please add the self-study tag. $\endgroup$ Commented Apr 7, 2023 at 15:57

1 Answer 1


Note that $K$ is the Hadamard product of the matrix $M = (m_{ij})$ with itself, where $m_{ij} = 1 + x_i^Tx_j$, which can be written as (assuming the input vector $x_i$ is a $p \times 1$ column vector): \begin{align} M = ee^T + XX^T, \end{align} where \begin{align} e = \begin{bmatrix} 1 \\ 1 \\ \vdots \\ 1\end{bmatrix} \in \mathbb{R}^{n \times 1}, \quad X = \begin{bmatrix} x_1^T \\ x_2^T \\ \vdots \\ x_n^T \end{bmatrix} \in \mathbb{R}^{n \times p}. \end{align}

Hence for any $v \in \mathbb{R}^{n \times 1}$, we have \begin{align} v^TMv = v^Tee^Tv + v^TXX^Tv = (v^Te)^2 + (X^Tv)^T(X^Tv) \geq 0, \end{align} showing $M$ is positive semi-definite (PSD).

Now the result follows from $K = M \circ M$ and Schur product theorem:

If two matrices $M_1$ and $M_2$ are PSD, then their Hadamard product $M_1 \circ M_2$ is also PSD.

You attempt should also work, if assisted with some common "trace tricks" when dealing with quadratic forms (which is essentially the trick used by the first proof in the Schur product theorem link).

The second term $\sum_{i = 1}^n\sum_{j = 1}^n v_ix_i^Tx_jv_j$ is actually the Euclidean norm of the vector $v_1x_1 + \cdots + v_nx_n$, hence it is nonnegative.

To prove $\sum_{i = 1}^n\sum_{j = 1}^n v_i(x_i^Tx_j)^2v_j \geq 0$, denote the order $p$ matrix $\sum_k v_kx_kx_k^T$ by $A$, which is clearly symmetric. By the linearity of the trace operator $\operatorname{tr}$ and its property $\operatorname{tr}(M_1M_2) = \operatorname{tr}(M_2M_1)$, we have \begin{align} & \sum_{i = 1}^n\sum_{j = 1}^n v_i(x_i^Tx_j)^2v_j \\ =& \sum_{i = 1}^n\sum_{j = 1}^n v_ix_i^Tx_jx_i^Tx_jv_j \\ =& \sum_{i = 1}^n\sum_{j = 1}^n v_ix_i^Tx_jx_j^Tx_iv_j \\ =& \sum_{i = 1}^nv_ix_i^TAx_i \\ =& \sum_{i = 1}^n\operatorname{tr}(v_ix_i^TAx_i) \\ =& \sum_{i = 1}^n\operatorname{tr}(v_iAx_ix_i^T) \\ =& \operatorname{tr}\left(A\sum_{i = 1}^nv_ix_ix_i^T\right) \\ =& \operatorname{tr}(A^2) = \operatorname{tr}(A^TA) \geq 0. \end{align} This completes the proof.

  • $\begingroup$ +1. I think it would help many readers to expand your first line to explain that $K$ is the Hadamard product of $M$ with itself. Otherwise, your meaning is not evident until the very end of your post. $\endgroup$
    – whuber
    Commented Apr 7, 2023 at 16:52
  • $\begingroup$ @whuber good point, edited. $\endgroup$
    – Zhanxiong
    Commented Apr 7, 2023 at 16:54
  • $\begingroup$ Your proof is beautiful and valid not only for second order but for all degrees. Thank you very much. Do you think my attempt is too complex and a dead-end, or is there a trick to simplify it and arrive at a clear solution like yours? $\endgroup$
    – Muhteva
    Commented Apr 7, 2023 at 17:44
  • $\begingroup$ @Muhteva In my experience, directly evaluating $v^TKv$ as you did to prove the PSD of $K$ is very rare (unless for very trivial examples). Usually tricks are needed (e.g., apply some known inequalities or theorems like in this question). Another common and interesting trick is express the matrix entry as integrals, see this example and this example. $\endgroup$
    – Zhanxiong
    Commented Apr 7, 2023 at 18:02
  • 1
    $\begingroup$ @Muhteva After a second thought, when the order is 2, direct evaluation is also feasible (but some trick is still needed). See my addendum. $\endgroup$
    – Zhanxiong
    Commented Apr 7, 2023 at 19:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.